2022
DOI: 10.7717/peerj-cs.1074
|View full text |Cite
|
Sign up to set email alerts
|

A user satisfaction model for mobile government services: a literature review

Abstract: User satisfaction is essential for the success of an organisation. With the development of government service delivery through mobile platforms, a compatible measurement model must be found to measure user satisfaction with performing such services through a mobile government portal. Measuring user satisfaction with mobile government services is necessary nowadays due to the increasing popularity of smart devices. Research on mGovernment users’ satisfaction is lacking, leading to difficulties in understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…Performance is done in accordance with the expectations of the users, which involves punctuality, providing the same service to all users without errors, a sympathetic attitude, and high accuracy. These findings are consistent with researchers such as Al Radaideh (2011), Jaeger and Matteson (2009), Gemino et al (2004), Myint (2022), Desmal et al (2022), Akkaya et al (2013), Lee and Lin (2005), and Ferrerc et al (2019).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Performance is done in accordance with the expectations of the users, which involves punctuality, providing the same service to all users without errors, a sympathetic attitude, and high accuracy. These findings are consistent with researchers such as Al Radaideh (2011), Jaeger and Matteson (2009), Gemino et al (2004), Myint (2022), Desmal et al (2022), Akkaya et al (2013), Lee and Lin (2005), and Ferrerc et al (2019).…”
Section: Discussionsupporting
confidence: 90%
“…Myint (2022) revealed that e‐government service quality and customer satisfaction could be guaranteed by the existence of eight contributing dimensions: system quality, reliability, security, accessibility, information quality, service capability, interactivity, and responsiveness. Desmal et al (2022) confirmed this relationship, describing that by the fact that reliability is one of the government qualities factors that can measure the system performance using the attributes of timeliness, accuracy, error‐free, service promise, and confidentiality, which in turn guarantee the customer's satisfaction. Akkaya et al (2013) also ensured this relationship; they mentioned that reliability is one of the most important factors affecting service quality and customer satisfaction.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 95%
See 3 more Smart Citations